What's Trust Got to do with it? Measuring Levels of Political Trust in South Africa 20 Years after Democratic Transition. (2nd January 2016) - Gouws, Amanda; Schulz-Herzenberg, Collette
ABSTRACT: Democratic consolidation relies on a degree of political trust and support for new democratic institutions and actors. A decline in political trust threatens the legitimacy of institutions, and democracy itself. Using Ipsos Khayabus 2014 national public opinion survey data, the paper explores levels of political trust in South Africa's transitional society in late 2014. It asks whether there is a sufficient mass of 'critical citizens' to ensure accountable government, and trust expressed towards key objects in the political system. We find that a majority of South Africans are critical citizens, offering conditional support based on performance evaluations. However, we also find little distinction in the minds of citizens between political institutions and the actors that inhabit them. Low levels of trust in political actors tend to erode trust in institutions. In turn, political trust in democratic institutions is also linked to evaluations of the ruling party; signalling the dangers of a prolonged stay in power by a dominant party. Finally, we conclude with possible implications for democratic consolidation by arguing that if despondence with current actors and institutions increases citizens may become less satisfied with democracy and less inclined to embrace the dream of a democratic, unified nation.